2012
DOI: 10.1177/0022034512461796
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Plasma/Serum IgG Test to Screen for Periodontitis

Abstract: Chronic periodontitis is a silent infectious disease prevalent worldwide and affects lifestyle-related diseases. Therefore, efficient screening of patients is essential for general health. This study was performed to evaluate prospectively the diagnostic utility of a blood IgG antibody titer test against periodontal pathogens. Oral examination was performed, and IgG titers against periodontal pathogens were measured by ELISA in 1,387 individuals. The cut-off value of the IgG titer was determined in receiver op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 20 publications
3
93
3
Order By: Relevance
“…In addition to the periodontal examination, a blood IgG antibody titer assay for periodontal pathogens with an enzyme-linked immunosorbent assay (ELISA), as previously described, was used to assess the degree of periodontal disease based on the detection of humoral immunologic responses accompanying the elevation in the serum IgG antibody titers against periodontal pathogens. 11,12 The results showed that the IgG antibody titer against A actinomycetemcomitans Y4, the B strain of A actinomycetemcomitans, which is frequently associated with AgP, was 4.85 times higher than the mean of 2 SD of the values observed in the healthy controls in a previous report (Fig 1, C). 12 The patient was therefore diagnosed with generalized AgP, possibly caused by A actinomycetemcomitans Y4.…”
Section: Diagnosis and Etiologymentioning
confidence: 51%
“…In addition to the periodontal examination, a blood IgG antibody titer assay for periodontal pathogens with an enzyme-linked immunosorbent assay (ELISA), as previously described, was used to assess the degree of periodontal disease based on the detection of humoral immunologic responses accompanying the elevation in the serum IgG antibody titers against periodontal pathogens. 11,12 The results showed that the IgG antibody titer against A actinomycetemcomitans Y4, the B strain of A actinomycetemcomitans, which is frequently associated with AgP, was 4.85 times higher than the mean of 2 SD of the values observed in the healthy controls in a previous report (Fig 1, C). 12 The patient was therefore diagnosed with generalized AgP, possibly caused by A actinomycetemcomitans Y4.…”
Section: Diagnosis and Etiologymentioning
confidence: 51%
“…To assess normal distribution, the Shapiro-Wilk test was used. The cut-off value of the titer obtained from the area under the receiver operating characteristic (ROC) curve [15] was set to 29, 39, and 49 the basis of a value of 1.68. The relation between atherosclerosis-related clinical markers in systemic examinations and severity of plasma IgG antibody level to P. gingivalis at baseline was analyzed by Student's t test for parametric data and Wilcoxon rank-sum test for non-parametric data using the groups by the individual cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…A blood sample was taken to ascertain Plasma IgG antibody titer to P. gingivalis FDC381. Blood sampling utilized the Plasma Antibody Titer Tests Using DEMECAL Ò Blood Test Set (Sunstar Inc. Osaka, Japan), and data were measured by Leisure, Inc. (Tokyo, Japan) by enzymelinked immunosorbent assay (ELISA) [15].…”
Section: Systemic Examination Of Lifestyle-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG titers against A. actinomycetemcomitans, P. intermedia, Eikenella corrodens (E. c.), and P. gingivalis were determined using an enzyme-linked immunosorbent assay. The details of the measurement method are described in detail elsewhere (33).…”
Section: Measurement Of Igg Titers Against Periodontal Bacteriamentioning
confidence: 99%